Morphofunctional changes in the lymphoid component of the rats prostate gland in conditions of immunostimulation - Evtushenko, V. M.; Syrtsov, V. K.; Popko, S. S.; Євтушенко, Валентина Михайлівна; Сирцов, Вадим Кирилович; Попко, Світлана Сергіївна; Евтушенко, В. М.; Сырцов, В. К.; Попко, С. С. (Дніпро : [б. в.], 2019)
To date, the state of the local immune system of the human prostate gland is not sufficiently studied, which prevents in-depth study of sexual disorders and infertility in men, as well as its common diseases: hypertrophy, adenoma, cancer. In order to study the morphological state of the lymphoid apparatus of the prostate of rats on the background of immunostimulation, 60 rat prostate glands were studied by histological, morphometric and statistical methods. Using the methods of variation statistics, we assessed the correctness of the distribution of signs for each of the obtained variation series, the average values for each attribute that was studied, standard errors and standard deviations. The reliability of differences in values between independent micrometric values with a normal distribution of signs was determined by the Student's criterion. The paper describes the patterns of formation of the local immune system of the prostate gland in the experiment after the introduction of immunoglobulin in adult male rats Wistar line. It was revealed that in rats after administration of immunoglobulin, the formation of lymphoid structures was observed three days earlier than in intact and control rats. First appear lymphoid formations in the stroma of the prostate gland, in the blood vessels - perivascular lymphoid nodules. By the end of the first week, lymphoid structures are formed in the glandular epithelium of the prostate gland - lymphoepithelial nodules. In lymphoid structures, the content of lymphocytes in all periods exceeds the benchmarks with the maximum changes on day 7 of the study. Reactive changes in the capillary endothelium in close relationship with the restructuring of lymphoid nodules during antigenic stimulation indicate that they are redundant in providing immune homeostasis. Thus, against the background of immunostimulation, changes occur in the local immune system of the prostate gland, manifested in an increase in the number of immunocompetent cells, the formation of lymphoid nodules, and are accompanied by corresponding changes in the hemomicrocirculatory bed. На сьогоднішній день стан локальної імунної системи передміхурової залози людини є недостатньо дослідженим, що перешкоджає поглибленому вивченню статевих розладів і безпліддя у чоловіків, а також її поширених захворювань: гіпертрофії, аденоми, раку. Мета роботи - вивчити морфологічний стан лімфоїдного апарату передміхурової залози щурів на тлі імуностимуляції. За допомогою гістологічних, морфометричних та статистичних методів дослідження були вивчені 60 передміхурових залоз щурів. Оцінили правильність розподілу ознак за кожним із отриманих варіаційних рядів, середні значення за кожною вивченою ознакою, стандартні помилки та стандартні відхилення. Достовірність різниці значень між незалежними мікрометричними величинами при нормальному розподілі ознак визначали за критерієм Ст'юдента. В роботі охарактеризовані закономірності формування локальної імунної системи передміхурової залози в експерименті після внутрішньом'язового введення імуноглобуліну у статевозрілих щурів лінії Вістар. Виявлено, що у щурів після введення імуноглобуліну лімфоїдні структури формуються на три доби раніше, ніж у інтактних і контрольних тварин. Спочатку з'являються лімфоїдні утворення в стромі передміхурової залози, а біля кровоносних судин - периваскулярні лімфоїдні вузлики. До кінця першого тижня лімфоїдні структури формуються в області залозистого епітелію передміхурової залози - лімфоепітеліальних вузликів. У лімфоїдних структурах вміст лімфоцитів в усі періоди перевищує контрольні показники з максимальними змінами на 7 добу дослідження. Реактивні зміни ендотелію капілярів в тісному взаємозв'язку з перебудовою лімфоїдних вузликів при антигенній стимуляції вказують на їх резервні можливості у забезпеченні імунного гомеостазу. Таким чином, на тлі імуностимуляції відбуваються зміни в локальній імунній системі передміхурової залози, котрі проявляються у збільшенні кількості імунокомпетентних клітин, формуванні лімфоїдних вузликів, і супроводжуються відповідними змінами гемомікроциркуляторного русла. На сегодняшний день состояние локальной иммунной системы предстательной железы человека исследовано недостаточно, что препятствует углубленному изучению половых расстройств и бесплодия у мужчин, а также ее распространенных заболеваний: гипертрофии, аденомы, рака. Цель работы - изучить морфологическое состояние лимфоидного аппарата предстательной железы крыс на фоне иммуностимуляции. С помощью гистологических, морфометрических и статистических методов исследования были изучены 60 предстательных желез крыс. Оценили правильность распределения признаков по каждому из полученных вариационных рядов, средние значения по каждому изученному признаку, стандартные ошибки и стандартные отклонения. Достоверность различий значений между независимыми микрометрическими величинами при нормальном распределении признаков определяли по критерию Стьюдента. В работе охарактеризованы закономерности формирования локальной иммунной системы предстательной железы в эксперименте после введения иммуноглобулина у половозрелых крыс линии Вистар. Выявлено, что у крыс после введения иммуноглобулина лимфоидные структуры формируются на трое суток раньше, чем у интактных и контрольных животных. Сначала появляются лимфоидные образования в строме предстательной железы, а возле кровеносных сосудов - периваскулярные лимфоидные узелки. К концу первой недели лимфоидные структуры формируются в области железистого эпителия предстательной железы - лимфоэпителиальных узелков. В лимфоидных структурах содержание лимфоцитов во все периоды превышает контрольные показателями с максимальными изменениями к 7 суткам исследования. Реактивные изменения эндотелия капилляров в тесной взаимосвязи с перестройкой лимфоидных узелков при антигенной стимуляции указывают на их резервные возможности в обеспечении иммунного гомеостаза. Таким образом, на фоне иммуностимуляции происходят изменения в локальной иммунной системе предстательной железы, проявляющиеся в увеличении количества иммунокомпетентных клеток, формировании лимфоидных узелков, и сопровождаются соответствующими изменениями гемомикроциркуляторного русла.
Морфофункціональні зміни лімфоїдного компонента передміхурової залози щурів в умовах імуностимуляції
Морфофункциональные изменения лимфоидного компонента предстательной железы крыс в условиях иммуностимуляции
Keywords: prostate gland; immunostimulation; lymphoid component; передміхурова залоза; імуностимуляція; лімфоїдний компонент; предстательная железа; иммуностимуляция; лимфоидный компонент